Performance and emission assessment of thermo-electric power plant for rotorcraft propulsion - Roumeliotis, Ioannis; Arena, Francesco; Liu, Yize; Vouros, Stavros; Pachidis, Vassilios; Broca, Olivier; Toure, Djiby; Unlu, Deniz (American Society of Mechanical Engineers (ASME), 2021)
This paper assesses a gas turbine based parallel rotorcraft hybrid electric propulsion system in terms of overall performance and emissions. Three different electric power train technology levels and three different power management strategies are considered for identifying the potential benefits of hybridization in relation to technology advancements and quantifying the effect of PMS. For this analysis, a Passenger Air Transport of a twin-engine medium helicopter is used. The propulsion systems mission simulation and emissions calculation are performed in Simcenter Amesim. The assessment framework integrates a thermal power-plant model, an electric power plant model for the hybrid electric cases, a helicopter simulation model and suitable pollutant emissions calculation correlations. For establishing NOx emission correlations that can be used for turboshaft engine calculations, a systematic evaluation of different correlations available in the literature is performed. The correlations are compared for different operating points against a calibrated stirred reactor model. The suitable correlations are utilized in the framework. The propulsion system is sized according to the technology levels and power management strategy considered, updating the helicopter Take-Off Weight for each case. The results indicate that there is potential for efficiency betterment and CO2 emissions reduction. The benefits strongly depend on the power management strategy and energy and power density of the electric power train. For current technology level and for the cases examined herein no benefits in terms of overall performance and emissions accrue. If future technology level is considered, hybridization may offer benefits in terms of performance to the expense of NOx emissions for the case that the power train is used for boosting and the gas turbine is scaled down. Power splitting may offer block fuel, turbine life and NOx benefits to the expense of overall energy performance.